Rotação de culturas, propriedades físicas do solo e produtividade de grãos de feijão, milho e soja - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The plants yield is related to several factors, among these, soil tillage, soil compaction and crop rotation. The objective was to evaluate the influence of winter cover crops, crop rotation on soil physical properties and beans, corn and soybean yield for two years. Three experiments were carried out, each corresponding to bean, corn or soybean culture. Was used the randomized complete block design with three treatments and four replications consisting of plots of 3 x 10 m. The treatments were the managements: two systems of cover crops and crop rotation in no-till and without cultivation in winter in conventional tillage. The dry mass of the cover crops, soil physical properties and grain yield for beans, corn and soybean for two years were evaluated. Crop rotation systems and cover crops mostly increase yields of corn and soybeans. System with crop rotation in no-till increases soil compaction in the superficial layer compared to conventional tillage, but does not reduce the yield of beans, corn and soybean.
Keywords: Plantio direto; Plantas de cobertura; Phaseolus vulgaris; Zea mays; Glycine max; No-till; Cover crops; CNPQ::CIENCIAS AGRARIAS